2009
DOI: 10.1111/j.1440-1827.2009.02376.x
|View full text |Cite
|
Sign up to set email alerts
|

Anaplastic large cell lymphoma in leukemic phase: Extraordinarily high white blood cell count

Abstract: Anaplastic large cell lymphoma (ALCL) is a distinct type of T/null-cell non-Hodgkin lymphoma that commonly involves nodal and extranodal sites. The World Health Organization of lymphoid neoplasms recognizes two types: anaplastic lymphoma kinase (ALK) positive or ALK negative, the former as a result of abnormalities involving the ALK gene at chromosome 2p23. Patients with ALCL rarely develop a leukemic phase of disease, either at the time of initial presentation or during the clinical course. Described herein i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 19 publications
2
37
0
Order By: Relevance
“…Its clinical features include significant respiratory distress, diffuse lung infiltrates or pleural effusions, and hepatosplenomegaly. Although ALK positivity is generally associated with a favorable outcome, leukemic ALK-positive ALCL has a highly aggressive clinical course and a poor outcome (16)(17)(18). We were able to closely follow the clinical course of the present patient as she regularly visited our hospital for the treatment of pancytopenia; we observed that the development and progression of the lymphoma was remarkably rapid in the leukemic phase.…”
Section: Discussionmentioning
confidence: 66%
“…Its clinical features include significant respiratory distress, diffuse lung infiltrates or pleural effusions, and hepatosplenomegaly. Although ALK positivity is generally associated with a favorable outcome, leukemic ALK-positive ALCL has a highly aggressive clinical course and a poor outcome (16)(17)(18). We were able to closely follow the clinical course of the present patient as she regularly visited our hospital for the treatment of pancytopenia; we observed that the development and progression of the lymphoma was remarkably rapid in the leukemic phase.…”
Section: Discussionmentioning
confidence: 66%
“…While leukemic peripheral blood involvement is rare in ALCL, an association has been reported with small-cell variants [5, 6, 11], which may be a potential explanation for the poor prognosis and aggressive nature of small-cell variant ALCL. Extreme leukocytosis involving neutrophils and atypical lymphocytes is usually the feature noted in the peripheral blood.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike intravascular B‐cell lymphoma, a well‐defined entity, intravascular T‐cell lymphoma is not included in the current classification of lymphomas and its revision, probably due to the very small number of cases thoroughly characterized and reported. Moreover, most cases reported as intravascular T‐cell or natural killer (NK)‐cell lymphomas actually are leukemic presentation or variants of other types of lymphoma, mainly NK/T‐cell lymphoma, anaplastic large cell lymphoma (both anaplastic large cell kinase positive and negative types), or a recently described CD30 positive intravascular T‐lymphoproliferative disorder involving the skin . An additional level of complexity is added by the wide geographical distribution of the cases and by the lack of a homogenous work‐up.…”
Section: Introductionmentioning
confidence: 99%